Multi-omics analysis reveals the effects of microbiota on oral homeostasis - Long, Huiqing; Yan, Li; Pu, Juncai; Liu, Yiyun; Zhong, Xiaogang; Wang, Haiyang; Yang, Lu; Lou, Fangzhi; Luo, Shihong; Zhang, Yingying; Liu, Yang; Xie, Peng; et al. (Frontiers in Immunology, 2022)
The oral epithelium’s normal morphological structure and function play an important role in maintaining oral homeostasis, among which microbiota and chronic stress are key contributing factors. However, the effects of microbiota and chronic stress on the morphological structures and molecular function of oral homeostasis remain unclear. In this study, morphological staining was used to compare the tongue structure of specific pathogen-free and germ-free mice, and an integrated multi-omics analysis based on transcriptomics, proteomics, and metabolomics was performed to investigate the regulatory mechanisms of microbiota and chronic stress on oral homeostasis. We found that the morphological structure of the tongue in germ-free mice was disordered compared with in specific pathogen-free mice, especially in the epithelium. Multi-omics analysis indicated that differentially expressed molecules of the tongue between germ-free and specific pathogen-free mice were significantly enriched in the mitochondrial metabolic process and immune response. Interestingly, microbiota also significantly influenced the permeability of the oral epithelial barrier, represented by the differential expression of keratinization, and cell adhesion molecules. It was worth noting that the above changes in the tongue between specific pathogen-free and germ-free mice were more significant after chronic stress. Collectively, this is the first study to reveal that the microbiota might maintain oral homeostasis by reshaping the structure of the oral epithelial barrier and changing the function of molecular biology, a process that may be driven by the immune response and mitochondrial metabolic process of oral tissue. Furthermore, chronic stress can enhance the regulatory effects of microbiota on oral homeostasis.